Bhutan Development Report, January 2019 : A Path to Inclusive and Sustainable Development - World Bank Group (World Bank, Washington, DC, 2019)
Bhutan has a strong track record of reducing poverty and boosting shared prosperity, primarilysupported by the state, which has played a large role in the country's development accomplishments.Growth has been driven mainly by the public sector through hydropower development. Statedominance is also reflected in the existence of a large number of state-owned enterprises (SOEs).However, the dependence on hydropower has resulted in a weak private sector and also createdmacroeconomic vulnerabilities. The high import content of hydropower construction widened theexternal imbalance and increased indebtedness. In addition, tax collection at 14 percent of grossdomestic product (GDP) in 2017/18 is low by international standards. The government has taken important steps to develop the nascent private sector through investments in infrastructure and improvements in the investment climate. It has also invested heavily in education and health. Despite these laudable investments, available jobs remain vacant, while educated youthremain unemployed. While hydropower will remain dominant in the foreseeable future, Bhutan'sdemographic transition requires more concerted efforts to develop the private sector.